MEMBACA PERKAWINAN MASYARAKAT ISLAM SASAK DARI PERSPEKTIF INTERLEGALITAS HUKUM - Murdan, Murdan (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
This paper will discuss the side of the interlegality and interlaw among customary law, religious law and state law in tribal societies in Indonesia, which is focused on the marriage of Sasak people. As an Indonesian local community, the Sasak community has their own local laws in undergoing interactions and social contracts between each other, especially in matters of marriage. Along with the embrace of Islam by the Sasak community, the Islamic law also contributes in decorate every process of the marriage. In addition to the existence of customary law and Islamic law that adorn the marriage of the Sasak community, there is also a modern legal tradition, namely state law. As part of the Indonesian society, the Sasak people cannot escape the great influx of modern legal tradition or national law positivism, which is directly echoed by the state. Departing from this illustration, the discussion in this paper includes: the interlegality between Sasak customary law and religious law (Islamic law); the interlegality between Sasak customary law and state law; and the last is the interlegality among Sasak customary law (local legal order), religious law (Islamic law/Islamic legal order), and state law (state legal order).Tulisan ini akan membahas sisiinterlegalistikantara hukum adat, hukum agama dan hukum negara pada masyarakat kesukuan di Indonesia, yang difokuskan pada perkawinan masyarakat suku Sasak. Sebagai masyarakat lokal Indonesia, masyarakat Sasak memiliki hukum lokal sendiri dalam menjalani intraksi dan kontrak sosial antara satu sama lain, khususnya dalam persoalan perkawinan. Seiring dengan dipeluknya agama Islam oleh masyarakat Sasak, maka hukum Islam pun memberi andil dalam menghiasi setiap proses-proses perkawinan itu. Selain keberadaan hukum adat dan hukum Islam yang menghiasi perkawinan masyarakat Sasak, terdapat juga tradisi hukum modern, yakni hukum negara. Sebagai bagian dari masyarakat Indonesia, masyarakat Sasak tidak bisa melepaskan diri dari arus besar legisme atau positifisme hukum nasional, yang secara langsung digaungkan oleh negara. Berangkat dari ilustasi ini, maka pembahasan dalam tulisan ini meliputi: interlegalistik antara hukum perkawinan adat Sasak dan hukum agama (Hukum Islam); interlegalistik antara hukum perkawinan adat Sasak dan hukum negara; dan terakhir adalah interlegalistik antara hukum perkawinan adat Sasak, hukum agama (hukum Islam), dan hukum negara.